A Review on Enterocin DD14, the Leaderless Two-Peptide Bacteriocin with Multiple Biological Functions and Unusual Transport Pathway - Rabia Ladjouzi; Elodie Dussert; Radja Teiar; Yanath Belguesmia; Djamel Drider (MDPI AG, 2023)
Enterocin DD14 (EntDD14) is a two-peptide leaderless bacteriocin (LLB) produced by Enterococcus faecalis 14, a human strain isolated from meconium. Studies performed on EntDD14 enabled it to show its activity against Gram-positive bacteria such as Listeria monocytogenes, Clostridium perfringens, Enterococcus faecalis, and Staphylococcus aureus. EntDD14 was also shown to potentiate the activity of different antibiotics such as erythromycin, kanamycin, and methicillin when assessed against methicillin-resistant Staphylococcus aureus (MRSA) in vitro and in vivo in the NMRI-F holoxenic mouse model. Additionally, EntDD14 has an antiviral activity and decreased the secretion of pro-inflammatory IL-6 and IL-8 in inflamed human intestinal Caco-2 cells. The genome of E. faecalis 14 was sequenced and annotated. Molecular tools such as Bagel4 software enabled us to locate a 6.7kb-EntDD14 cluster. Transport of EntDD14 outside of the cytoplasm was shown to be performed synergistically by a channel composed of two pleckstrin-homology-domain-containing proteins, namely DdE/DdF and the ABC transporter DdGHIJ. This latter could also protect the bacteriocinogenic strain against extracellular EntDD14. Here, we focus on academic data and potential therapeutic issues of EntDD14, as a model of two-peptide LLB.